STUDENTS’ SELF CONFIDENCE IN SPEAKING ENGLISH - Nety Nety; Asti Wahyuni B; Nurhaeni Nurhaeni (English Education Department, 2020)
This research intended to analyze factors of students’ lack of self confidence in speaking English. It was also aimed to present possible strategies used to overcome students’ lack of self confidence in speaking English. The type of this research was qualitative. This research was conducted in SMA Negeri 4 BauBau. This research focused on obtaining data from the English teacher and students at eleventh grade of SMA Negeri 4 BauBau in the academic year 2018/2019 as the subjects of the research. In collecting data, the researchers used observation, interview. The technique used in analyzing data were three steps, those were data reduction, data display, and conclusion drawing. The result of this research showed that the factors which cause students’ lack of self confidence were anxiety, shyness, fear of making mistakes, and lack of vocabulary. Meanwhile, the possible strtaegies to overcome students’ lack of self confidence in speaking English were lowering students’ anxiety in classroom, improving students’ vocabulary, boosting students’ self-confidence, and forming group discussion.